Phytopharmacological Updates on Mentha longifolia: A Comprehensive Review - Singh, Kehar; Sanduja, Mohit; Thakral, Sunil; Gaur, Rishabh; Kulshreshtha, Mayank (Free Radicals and Antioxidants)
Wild mint, or Mentha longifolia, is a well-known folk treatment. This plant's parts have been employed in Iranian and other traditional medicines. Numerous researches have demonstrated the plant's numerous pharmacological and medicinal properties. In order to review the traditional applications of M. longifolia as well as the pharmacological and therapeutic properties of its complete extract and key components, we prepared this study. An herb called Mentha longifolia has a wide range of pharmacological activities, including effects on the neurological system, gastrointestinal tract, and bacteria. Using Google, PubMed, Scholar, and other web resources, data were gathered.
Keywords: Mentha longifolia; Medicinal; Gastrointestinal; Neurological; Herb